Coping in mental health during social isolation: analysis in light of Hildegard Peplau - Eduardo Bassani Dal'Bosco; Lara Simone Messias Floriano; Amanda Gabrieli Schuber Spósito Rangel; Mirian Cristina Ribas; Ana Paula Garbuio Cavalheiro; Carla Luiza da Silva; Luciane Patricia Andreani Cabral (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the coping of individuals in social isolation due to suspicion or confirmation of coronavirus infection from the perspective of Hildegard Peplau's Theory of Interpersonal Relations. Methods: this is a qualitative, descriptive research, carried out with 34 individuals in social isolation due to suspicion or confirmation of coronavirus infection who passed through a screening tent of a university hospital in Paraná. Data were collected through semi-structured interviews in June and July 2020. Empirical categories were interpreted by content analysis. Results: four categories emerged: Distance; Social and emotional support; Self-awareness and resolution; Learning. These categories established the coping strategies. Conclusions: individuals undergoing social isolation are more likely to present problems related to mental health. It was highlighted that coping strategies, motivated by nurses, anchored in Hildegard Peplau's theoretical framework, promoted the necessary learning for promoting participants' mental health in the face of a pandemic context.